TINGKAT PENGANGGURAN TERBUKA PEREMPUAN DI KABUPATEN SUBANG - Frida Yulinda; Zaenal Hirawan; Kamal Ma’ruf (Jurnal Administrasi Publik, 2021)
Unemployment is a macroeconomic problem and an important contributor to hindering development and regional economies, both regencies and cities. Labor absorption that is not in accordance with the amount of available resources also causes the unemployment rate to be quite high. This study aims to identify the characteristics of female unemployment and the factors that cause unemployment in Subang Regency. The research method used is descriptive using secondary data from BPS Subang Regency in 2020. Female unemployment in Subang Regency is caused by the level of educational qualifications, skills, community culture and the capacity of the business world. The level of education and skills that are not evenly distributed, the inherent culture of the community that a woman becomes the foundation in managing the household. This dual function becomes less focus and access in market share and in the world of workforce.